Highly elastic and flexible transparent conductive films derived from latex copolymerization: P(SSNa-BA-St)/PEDOT/graphene. Issue 72 (20th December 2019) - Huang, Bo; Luo, Xinxin; Zou, Qichao; Wang, Suxiao; Zhang, Jinzhi
Abstract : We reported an transparent, water resistant, and flexible conductive materials P(SSNa-BA-St)/PEDOT/graphene and their conductivity are due to the large surface area to polymerize the extended PEDOT chain on the nanoparticles. Abstract : We reported an innovative transparent, elastic and flexible conductive composite materials P(SSNa-BA-St)/PEDOT/graphene which were prepared by using P(SSNa-BA-St) latex as template for PEDOT polymerization and graphene doping. This P(SSNa-BA-St)/PEDOT/graphene film exhibited highly transparent, good water resistance, low moisture adsorption, highly elastic and highly conductive properties, which can serve as a practical approach to fabricate the flexible, conductive and transparent films for wearable and implantable electronic devices, and photovoltaic cells.